2010
DOI: 10.1007/s00270-010-9924-9
|View full text |Cite
|
Sign up to set email alerts
|

Single-Institution Results of Image-Guided Nonplugged Percutaneous Versus Transjugular Liver Biopsy

Abstract: Both transjugular and percutaneous liver biopsy techniques are efficacious and safe. Contraindications such as thrombocytopenia, coagulopathy, and ascites are indicators of greater complications but are not necessarily prevented by transjugular biopsy. Percutaneous biopsy more frequently yields a diagnostic specimen than transjugular biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…[92][93][94] Comparative studies demonstrate that while the diagnostic adequacy of the samples is higher through PLB, samples obtained by TJLB are sufficient to make a diagnosis and equally safe. [95][96][97] Thus, in the presence of contraindications to PLB, TJLB provides an equally safe and adequate technique to obtain liver tissue, with cutting-type needles being preferred over aspiration-type needles.…”
Section: Transjugular Liver Biopsymentioning
confidence: 99%
“…[92][93][94] Comparative studies demonstrate that while the diagnostic adequacy of the samples is higher through PLB, samples obtained by TJLB are sufficient to make a diagnosis and equally safe. [95][96][97] Thus, in the presence of contraindications to PLB, TJLB provides an equally safe and adequate technique to obtain liver tissue, with cutting-type needles being preferred over aspiration-type needles.…”
Section: Transjugular Liver Biopsymentioning
confidence: 99%
“…However, TJLB is a limited technique as a result of small sample size and caliber, longer procedure time, and the need for a skilled interventional radiologist [18]. Furthermore, it is also not without complications, which arise when the liver capsule or capsular veins are perforated, and does not prevent this risk, and it actually seems to increase risk in ascitic patients [3]. Therefore, the TJLB still needs a further study to evaluate indication, technique and complications.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are two minimally invasive techniques for liver tissue sampling: imageguided percutaneous liver biopsy (PLB) and transjugular liver biopsy (TJLB) [1][2][3][4]. Both techniques have several disadvantages, such as the risk of bleeding and subcapsular hematoma in the former, and the small sample size, longer procedure time and the need for considerable interventional skill in the latter.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of such complications ranges from 0% to 20% [11]. Hardman et al [4] reported a large subcapsular hematoma caused by TJLB requiring embolization and prolonged admission. Lebrec et al [9] also reported a fatal case of intraperitoneal hemorrhage due to perforation of the liver capsule caused by excessive of the needle.…”
Section: Transjugular Liver Biopsy (Tjlb)mentioning
confidence: 99%
“…Several large studies have shown rates of major complication after PLB ranging from 0.09% to 2.3%, severe complications in 0.57%, and mortality ranging from 0.03% to 0.11% [23][24][25]. Hardman et al [4] reported one patient with graft vs. host disease and hypertension who died after PLB. This patient had multi-organ system failure at the time of biopsy and died within 24 hours of the biopsy.…”
mentioning
confidence: 99%